2015
DOI: 10.3390/ijms16047682
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Dietary Lipid and Phenotypic Feed Efficiency on the Expression of Nuclear and Mitochondrial Genes Involved in the Mitochondrial Electron Transport Chain in Rainbow Trout

Abstract: A 2 × 3 factorial study was conducted to evaluate the effects of dietary lipid level on the expression of mitochondrial and nuclear genes involved in electron transport chain in all-female rainbow trout Oncorhynchus mykiss. Three practical diets with a fixed crude protein content of 40%, formulated to contain 10% (40/10), 20% (40/20) and 30% (40/30) dietary lipid, were fed to apparent satiety to triplicate groups of either low-feed efficient (F120; 217.66 ± 2.24 g initial average mass) or high-feed efficient (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Nonetheless, some observations described the potential benefits on the mitochondria oxidative phosphorylation induced by the changes in protein expression described in our study. [70][71][72][73][74] We have also to report that we did not measure protein levels, as we focused on mRNA. However, it should be noted that mRNA levels are acknowledged as informative of protein expression and are currently widely employed, especially in in-human studies.…”
Section: Original Researchmentioning
confidence: 99%
“…Nonetheless, some observations described the potential benefits on the mitochondria oxidative phosphorylation induced by the changes in protein expression described in our study. [70][71][72][73][74] We have also to report that we did not measure protein levels, as we focused on mRNA. However, it should be noted that mRNA levels are acknowledged as informative of protein expression and are currently widely employed, especially in in-human studies.…”
Section: Original Researchmentioning
confidence: 99%
“…S3 ). Confirming this result, a recent study showed that dietary lipid affects the expression of COX1, COX2, ATP6, and ND1 by common transcription factors such as the peroxisome proliferator-activated receptor ( Eya et al, 2015 ). On the other hand, the group consisting of COX7A1, NDUFB1, ND6, and NDUFA1 was exclusively present in the Metazoa and was concentrated in a different subnetwork ( Fig.…”
Section: Resultsmentioning
confidence: 63%